CAMBODIAN EFL STUDENTS’ PERCEPTIONS OF FACTORS INFLUENCING PRONUNCIATION - Vong, Chandarey; Sam, Rany; Soy, Seth (LLT Journal: A Journal on Language and Language Teaching, 2024)
This study aims to explore students’ perceptions of factors influencing pronunciation. The study was designed quantitatively. The purposive sampling method was used, and 50 Cambodian EFL students at the National University of Battambang were selected as the sample. The questionnaire was designed in a semi-structured format. The data was analyzed by SPSS. The result showed that most participants believed learning English from a young age leads to better pronunciation. Interestingly, it indicated that the mother tongue (Khmer) influences English pronunciation since learners find it difficult to produce some sounds, especially the /th/sh/f/v/ sound in English, as these sounds do not exist in the sound system of Khmer. Additionally, the majority of the respondents believed that being exposed to an English-speaking environment, including real communication with English native speakers or access to English-speaking learning media, can enhance pronunciation. Last but not least, it was also assumed that feedback on pronunciation errors and motivation contribute to a positive learning process. Therefore, this study provides insight into effective pronunciation instruction.